A Study On Physical Changes The Traditional Houses of Minahasa And Toraja In Indonesia - Suharto, M F (Journal of Educational Method and Technology, 2019)
. The aim of this research is to identify the physical changes that occur on the traditional houses of Minahasa and Toraja, including factors that cause the physical changes. Furthermore, we analyze the possibility of significant similarities and differences that exist on both the traditional houses. Based on the purposive sampling studies and literature studies, the discussion and analysis of the physical changes will include the physical elements of architecture which consist of form (design), structure and construction, materials, layout plan, and ornament. The results of this study indicate that the technology development, the natural influence, physiological needs as well as an increase in the fulfillment of social needs and the development of civilization has affected the physical changes. Of all the elements of the architecture that have been reviewed, we found that not all elements occur of the same physical changes and significant.Â Keywords: Physical changes, Traditional houses, Minahasa, Toraja